Importance of work-related factors for post-retirement labour market participation - Anu Polvinen; Sanna Tenhunen (PLoS ONE, 2026)
Today’s pensioners are healthier than ever, and many participate in the labour market after retirement. Some pensioners continue to work for financial reasons, but in most cases the motives for work are other than financial. Many sociodemographic factors are associated with post-retirement employment, but less is known about the role of work-related factors. This study examines the relationship between work-related factors and post-retirement employment among individuals who have recently retired on an old-age pension. The study is based on a Finnish survey conducted in 2022 (response rate 68%), supplemented by register data on 3,196 individuals aged 63 and over who retired from paid employment with an old-age pension between 2019 and 2021. Logistic regression models were used to estimate how work-related factors are associated with post-retirement employment. Information on work-related factors pertains to the last job held before retirement. Higher job demands and lower social support were associated with a lower likelihood of working in retirement. A higher physical workload was associated with a higher likelihood of working in retirement, especially among those working for financial reasons. Shift work, part-time work, and temporary work before retirement were also associated with a higher likelihood of working. Managers and professionals were more likely to work in retirement than lower-grade non-manual workers. The findings of this study highlight the importance of work-related factors in post-retirement employment decisions. Policies aimed at promoting such employment should therefore focus on improving working conditions before retirement. Furthermore, since work-related factors are differently related to financial and non-financial retirement motives, policy frameworks should move beyond one-size-fits-all solutions.